On thermal distribution of MHD mixed convective flow of a Casson hybrid nanofluid over an exponentially stretching surface with impact of chemical reaction and ohmic heating - Algehyne, Ebrahem A.; Alamrani, Fahad Maqbul; Khan, Arshad; Khan, Khurshid Alam; Lone, Showkat Ahmad; Saeed, Anwar (Colloid and polymer science, 2024)
This work signifies insights into diverse phenomena relevant to fluid dynamics, heat transfer, and chemical reactions in advanced materials. This work aims to discuss the mixed convective Casson magneto-hydrodynamics (MHD) hybrid nanofluid flow on a surface which is stretching in an exponential manner. To mechanize the thermal behavior of flow, the Buongiorno model along with dissipative effects has been incorporated in the current problem. Suitable variables have been employed to change the system of leading equations into dimensionless form, and the homotopy analysis approach (HAM) has been employed for the solution of resultant equations. As the outcome of this work, it has been observed that velocity distribution is reduced with escalation in magnetic, mixed convection, porosity, and buoyancy ratio factors. Thermal profiles are escalated with growth in Brownian motion, thermophoresis, magnetic field, and radiation factors as well as Eckert number. A comparative analysis has also been conducted in this work and found an acceptable agreement among previous and current results.